Isoinertial resistance training for strength, power and endurance - Slade, A. (1997)
Content: Introduction to Isoinertial Resistance Training Hypertrophy / Endurance Phase Basic Strength Phase Strength / Power Phase Peaking / Competition Phase Endurance Training References